Corrections for photons attenuation and scattering for the extrapolation chamber for measurement of air-kerma strength of 125I brachytherapy source. (18th March 2021) - Liu, C.; Song, M.; Liu, Y.; Wang, H.; Wei, K.; Hang, Z.
Abstract: A type of extrapolation chamber was designed in China Institute of Atomic Energy, CIAE. The chamber was used for the measurement of the air-kerma strength of the medical radiation 125 I source on primary standard level. In order to obtain the air-krema strength with a low uncertainty, some correction factors such as photon attenuation and scattering are needed to calculate. Correction factors for different types of 125 I seeds were estimated with increasing chamber depth. Based on the relation between ionization current and average photon fluence, attenuation correction factors were calculated with the analytical solution. Additionally, the scattering correction factors were estimated by a suitable method of Monte Carlo simulation. Photon attenuation includes four components. katt-volume, katt-foil, katt-sf, and katt-Al . The differences of correction factors are concerned, mainly due to the variation of chamer depths and 125 I seed types. katt-volume increases from 1.001 to 1.005. katt-foil varies between 1.0012 and 1.0014. katt-sf changes from 1.015 to 1.018. katt-Al varies between 1.038 and 1.048, which largely depend on the photon spectrum from the source. Meanwhile, the geometric dimension of the ionization chamber has a great influence on the scattering correction factors. The ksca values vary from 0.9960 to 0.9964 with different chamber depths, which only has 0.04% fluctuation.